Penatalaksanaan Penyakit Skabies Pada Laki-Laki Usia 42 Tahun Dengan Pendekatan Kedokteran Keluarga - Bahesty Cut Nyak Din; Sahab Sibuea (CV. Jasa Sukses Abadi, 2020)
Scabies is an infectious disease caused by infestation of Sarcoptes scabiei hominis variants and their products. Scabies is transmitted through direct skin-to-skin contact or indirect contact through shared objects, such as towels, clothing, bed linen. Lack of knowledge and personal hygiene can lead to scabies. This study is a case report based on Evidence Base Medicine in male patients aged 42 years by identifying risk factors and clinical problems and management of patients based on patient problems as well as the patient centered approach and family approach. Primary data were obtained through history taking (autoanamnesis), physical examination and home visits. Secondary data was obtained from the patient's medical record. Assessment is based on a holistic diagnosis from the beginning, process, and end of study in a qualitative and quantitative manner. Tn.Y patient aged 42 years was diagnosed with scabies, has an internal risk aspect in the form of the habit of rarely washing his hands after the activity and habit of using toiletries together. Aspects of external risks in the form of a dense residential environment, slums, and irregular arrangement of goods and there are similar complaints in the families of patients who live at home. Holistic management with a family doctor approach can improve knowledge, attitudes, and behavior in patients. In addition, the role of the family is very important in the care and treatment of sick family members.